Entrepreneurship Education: Embedding Practitioner Experience - Lester LLOYED - REASON; Roger MUMBY - CROFT; Leigh SEAR (Revista de Management Comparat International)
In a report recently produced by the National Council for Graduate Entrepreneurship (NCGE), the National Endowment for Science, Technology and the Arts (NESTA) and the Council for Industry and Higher Education (CIHE) concluded that ‘Entrepreneurship education is currently taught primarily through modules in business school courses and extra-curricular activities. HEIs need to enhance the perception and relevance of entrepreneurship education, so students and staff recognise the value of its combination of innovation, creativity, collaboration and risktaking skills to a wide range of disciplines’. This paper focuses on a ground breaking programme specifically designed to address these criticisms of the way in which enterprise and entrepreneurship is taught in universities. There are a huge number of programmes on offer across within European Higher Education with the words ‘enterprise’ and ‘entrepreneurship’ in the title, but what makes the BA (Hons) Enterprise and Entrepreneurial Management unique is the close involvement of entrepreneurs right from the outset, including course design, module content and delivery. This is achieved through an ‘entrepreneur in residence’ network, with Walter Herriot, Managing Director of St John’s Innovation Centre, Cambridge, one of the world’s leading incubation centres, as Director. This enables leading entrepreneurs to be embedded in fabric of the programme through playing a very active role in the continued development of the curriculum, content, and delivery of the pathway. Additionally, each student is allocated an entrepreneur as mentor for the duration of the three year programme. This paper will firstly explore the key issues raised by the policy community and others calling into question the appropriateness of the way in which enterprise and entrepreneurship is taught. It will then look at the way in which UK universities are responding to these comments. The paper concludes with a case study of an academic programme developed and delivered jointly by academics and practitioners.